An Overview on Sintering Technique in Pharmaceutical Sciences - Mohanty, Chandan; Patnaik, Soumya Stuti (Advanced Concepts in Pharmaceutical Research Vol. 9, 2024)
Sintering is the mechanism that strengthens the mechanical properties of consolidated pharmaceutical powders at high temperatures, forms solid bonds during tablet compression, and causes thermal curing in polymer-latex film coatings, according to pharmaceutical science. The concept of sintering was applied in the investigation of the effect of heating on the mechanical properties of pharmaceutical powders. The formation of solid bonds within a powder bed during tablet compression was studied in terms of sintering. The sintering process has been used for the fabrication of sustained–release matrix tablets and for the stabilization of the drug permeability of film coatings derived from various pharmaceutical lattices. Drug release characteristics from the sintered matrix tablets were inversely related to the sintering temperature and sintering duration. As the temperature of sintering and duration of sintering increased, the time required to attain maximum release from tablets also increased accordingly. The changes in the microstructures, hardness, friability, wettability, disintegration time and dissolution rate of tablets stored at elevated temperatures were also described as a result of sintering. Sintering conditions markedly affected the drug release properties depending upon the duration and temperature of sintering. The use of this sintering technique adds to the effectiveness of polymers for controlling drug release and provides a significant and expedient method for control release in oral dosage form.